Invasive Pseudomembranous Aspergillus Tracheobronchitis Accompanied With Fever and Hemoptysis: A Case Report - Xiaolong Li; Xin Wang; Shuhao Xu; Yinhe Feng; Yuanyuan Liu; Chunfang Zeng (Clinical Case Reports)
ABSTRACT Pseudomembranous Aspergillus tracheobronchitis is a relatively rare disease, and it is very easy for clinicians to misdiagnose. It is particularly necessary for the patient presenting with recurrent pyrexia and hemoptysis in the absence of clear‐cut pulmonary radiological findings to receive a bronchoscopy.